Faktor yang Berhubungan dengan Personal Hygiene Saat Menstruasi - Andri Setiya Wahyudi; Candra Panji Asmoro; Ira Suarilah (Jurnal Kesehatan Manarang, 2018)
Adolescents are a transition to adulthood with changes in growth and development. adolescents are at risk of reproductive health especially during menstruation. Personal hygiene during menstruation is the issue of determinants of adolescent health that affect the life of old age, management of disorders at the time of menstruation is to familiarize themselves hygienic behavior. The aim of this research is to know factors related to Personal hygiene during menstruation, such as knowledge, peer communication, menarche age and belief in mythology at siswi in MI Miftahul Ulum Pamekasan. Quantitative research type with cross sectional approach. Respondents in the study were MI Miftahul Ulum Pamekasan as many as 117 siswi. The measuring tool used is questionnaire and tested using Chi Square Sampling is done by purposive sampling method. The results showed that 76.1% of respondents have enough Personal hygiene categories and as many as 23.9% of respondents into the category of Personal hygiene is less. The Chi Square test shows that there is a relationship between knowledge (p = 0.001), peer communication (p = 0.002), and mythic belief (p = 0.001) with Personal hygiene during menstruation, and menarche age (p = 0.473) Personal hygiene during menstruation. Teenagers are expected to increase Personal hygiene during menstruation by providing knowledge gained from mass media, parents, health workers and books. Schools apply health education methods to improve Personal hygiene during menstruation like SGD (Small Group Discussion).